2001
DOI: 10.1182/blood.v97.3.660
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the biomechanical properties of neutrophils and endothelial cells during adhesion

Abstract: This study examined changes in the biomechanical properties of cultured pulmonary microvascular endothelial cells (ECs) and neutrophils induced by adhesion of neutrophils to these ECs. The biomechanical properties of cells were evaluated using magnetic twisting cytometry, which measures the angular rotation of ferromagnetic beads bound to cells through antibody ligation on application of a specified magnetic torque. Adhesion of neutrophils to 24-hour tumor necrosis factor-␣ (TNF-␣)-treated ECs, but not to untr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 50 publications
(60 reference statements)
2
51
1
Order By: Relevance
“…Wang et al (30) have reported that the endothelium increases in rigidity and perhaps contributes to the physical trapping of the general circulating pool of leukocytes. There may also be a direct increase in leukocyte rigidity in response to LPS and thereby increased sequestration within the pulmonary microvascular bed (30). Clearly, it is not surprising that some studies have reported only partial or no decrease in LPS-induced leukocyte sequestration with anti-adhesion therapy (13,31).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (30) have reported that the endothelium increases in rigidity and perhaps contributes to the physical trapping of the general circulating pool of leukocytes. There may also be a direct increase in leukocyte rigidity in response to LPS and thereby increased sequestration within the pulmonary microvascular bed (30). Clearly, it is not surprising that some studies have reported only partial or no decrease in LPS-induced leukocyte sequestration with anti-adhesion therapy (13,31).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned in the preceding paragraph, neutrophil adhesion to human pulmonary microvascular endothelial cells (HPMVEC) treated with TNF-␣ also leads to endothelial cell stiffening and F-actin reorganization. Interestingly, unlike HUVEC monolayers, endothelial stiffening does not appear to rely on MLCK or MLC phosphorylation (280). This may reflect phenotypic differences between HUVEC and HPMVEC.…”
Section: Neutrophil Migration Across Vascular Endotheliummentioning
confidence: 99%
“…ECs were grown to confluence and used 2-3 days post-confluence. These cells can be induced to up-regulate ICAM-1 expression upon TNF-␣ stimulation (17,18).…”
Section: Methodsmentioning
confidence: 99%
“…Cultivation of Human Pulmonary Microvascular ECs-Human pulmonary microvascular ECs were obtained from Clonetics (Walkersville, MD) and plated onto fibronectin-coated culture dishes, as described previously (17,18). ECs were used between passage 7 and 15.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation